2020
DOI: 10.1038/s41467-020-16230-8
|View full text |Cite
|
Sign up to set email alerts
|

The scaffold protein p62 regulates adaptive thermogenesis through ATF2 nuclear target activation

Abstract: During β-adrenergic stimulation of brown adipose tissue (BAT), p38 phosphorylates the activating transcription factor 2 (ATF2) which then translocates to the nucleus to activate the expression of Ucp1 and Pgc-1α. The mechanisms underlying ATF2 target activation are unknown. Here we demonstrate that p62 (Sqstm1) binds to ATF2 to orchestrate activation of the Ucp1 enhancer and Pgc-1α promoter. P62Δ69-251 mice show reduced expression of Ucp1 and Pgc-1α with impaired ATF2 genomic binding. Modulation of Ucp1 and Pg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…Mutations in the p62 gene are strongly associated with Paget's disease of the bone (19), murine myeloid leukemia progression (20), neurodegenerative disease (21), obesity (22), vascular senescence (23), aging pathologies and cancer (24,25). p62 consists of 440 amino acids covering more than 10 domains and binding sites; hence, it is a key center of regulating multiple activities of cells, such as insulin signaling, energy balance, adipogenesis, brown adipose tissue (BAT) thermogenesis, inflammation, oxidative stress, apoptosis, etc (26)(27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in the p62 gene are strongly associated with Paget's disease of the bone (19), murine myeloid leukemia progression (20), neurodegenerative disease (21), obesity (22), vascular senescence (23), aging pathologies and cancer (24,25). p62 consists of 440 amino acids covering more than 10 domains and binding sites; hence, it is a key center of regulating multiple activities of cells, such as insulin signaling, energy balance, adipogenesis, brown adipose tissue (BAT) thermogenesis, inflammation, oxidative stress, apoptosis, etc (26)(27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%
“…With respect to metabolism, our previous results showed that total body inactivation of p62 resulted in mature-onset obesity due to reduced energy expenditure (EE) 14 , 15 . We also demonstrated that the selective inactivation of p62 in adipocytes, and also specifically in BAT, recapitulated the impaired EE and the obesity phenotype of total body knockout (KO) mice 16 18 . Therefore, adipocyte’s p62 emerges as a critical regulator of energy balance and adiposity in vivo.…”
Section: Introductionmentioning
confidence: 76%
“…We reported previously that the obese and insulin-resistant phenotypes observed in the whole-body p62 deficiency resulted from reduced systemic EE 14 that underscores the critical role of adipocyte’s p62 in sustaining β3-adrenergic signaling-induced mitochondrial function and thermogenesis in BAT 16 , as well as cancer-associated browning of subcutaneous WAT 17 . Importantly, the impaired thermogenesis is not secondary to the obese phenotype because impaired EE has previously been demonstrated in newborn p62 mutant pups and in young p62 mutant mice that yet do not differ in body weight or body composition 18 . Further evidence has been shown in isolated and in vitro cultured brown and inguinal white adipocytes harvested from either young lean non-obese p62 mutant mice 16 , 18 or neonates from this study.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Lu et al have identified artemether as an activator of browning and thermogenesis in vitro , which significantly enhances the metabolism of mice, as indicated by the insulin tolerance test (ITT) and glucose tolerance test (GTT) results ( Lu et al, 2016 ). To further evaluate the pharmacological potential, Lu et al found that artemether and other artemisinin derivatives induce C3H10T1/2 cell browning by activating the p38 mitogen-activated protein kinase (MAPK)/activating transcription factor-2 (ATF2) axis and deactivating the Akt/mTOR pathway, which has suggested to be involved in various anabolic and catabolic processes ( Cai et al, 2016 ; Lu et al, 2016 ; Fischer et al, 2020 ; Toda et al, 2020 ). Moreover, one-step qPCR suggested that the relative mRNA levels of browning-related genes, such as PR domain containing 16 (PRDM16), uncoupling protein 1 (UCP1) and peroxisome proliferator-activated receptor γ coactivator-1α (PGC-1α), were elevated after treatment with artemether, indicating that the increased thermogenesis in brown fat may also cause weight loss and enhance the metabolism in artemether-treated mice ( Lu et al, 2016 ).…”
Section: Type 2 Diabetesmentioning
confidence: 99%